Role of magnetic resonance spectroscopy and diffusion-weighted imaging in characterizing intra axial brain tumours - S., Soorya Prakash; Kattoju, Sudhakar (International Journal of Research in Medical Sciences, 2023)
Background: Magnetic Resonance imaging (MRI) is essential for assessing intracranial malignancies, but conventional MRI has limitations in tumour grading and infiltration information. Advanced Magnetic Resonance (MR) sequences, such as diffusion-weighted (DW) and Magnetic Resonance spectroscopy (MRS), can differentiate between low-grade and high-grade tumours, aiding treatment decisions. This study aims to evaluate the efficacy of diffusion-weighted imaging and magnetic resonance spectroscopy in grading intra-axial brain tumours and correlating the results with histopathology. Methods: This retrospective study involved 45 patients over one year at Apollo Hospital. MR imaging included conventional sequences, DW, and MRS with localizers in all three planes. DWI and ADC maps were obtained using specific b-values. Standard mean Apparent Diffusion Coefficient (ADC) values were automatically calculated for intra-lesional and peri-lesional regions. Results: Intralesional ADC values did not significantly differ between high-grade primary tumours (0.4-1 x 10-3 mm2/s, mean 0.7) and metastases (0.4-0.8 x 10-3 mm2/s, mean 0.7). However, peri-lesional ADC values were lower in primary tumours (0.3-1.3 x 10-3 mm2/s, mean 0.8), indicating peri-lesional infiltration, while higher in metastases (1.2-1.6 x 10-3 mm2/s, mean 1.4) due to the absence of peri-lesional infiltration. Additionally, intralesional ADC values showed a significant difference between low-grade tumours (1-2 x 10-3 mm2/s) and high-grade tumours (0.4-1 x 10-3 mm2/s), allowing for their distinction. There were significantly increased Cho/NAA and Cho/Cr ratios in high-grade tumours compared to low-grade tumours. Conclusions: MR spectroscopy and DWI with computation of ADC values can enhance the diagnostic effectiveness of MR imaging in detecting and grading malignant brain tumours.